Literasi Hazard dan Proteksi Kebakaran Bagi Siswa SMK Muhammadiyah 01 Padang - Ana Susanti Yusman; Febrimen Herista; Asiya Nurhasanah Habirun (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Muhammadiyah 01 Vocational High School Padang is the school with engineering concentration such as automotive, electrical, computer and network technology. The potential of hazards for school are: fire; exposure to radiation, electrical, and physical and the high potential places are : workshops, laboratories and classrooms. In addition, knowledge of HAZARD / Fire was given for 14 students of year X of SMK Muhammadiyah 01 Padang from various majors. The methods were used lecture and discussion. We did pretest and posttest in order to have participants knowledge. To sum up students' understanding of Hazard in general was 42% during the pre-test and increased to 50% during the post-test. However, the data were analyzed statistically and showed that there was an increase, constant and decrease of student understanding as follows: an increase from 25% to 75% for TBSM students (Motorcycle Business Engineering); constant 100% for RPL (Software Engineering) students; constant 30% for TITL students (Electrical Installation Engineering); constant 30% for TKJ (Computer and Network Engineering) students and a decrease from 60% to 30% for TPM (Mechanical Engineering) students. In conclusion, students of RPL, TKJ and TPM need to be given intense training on HAZARD and fire protection to improve their skills.